Exploration of The Species Richness of Dragonfly (Hexapoda: Odonata) in The Rice Field Ecosystem of Perian village, Montong Gading, East Lombok - Mohammad Liwa Ilhamdi; Aria Rizki Ivansyah; Muhammad Syazali (Jurnal Biologi Tropis, 2023)
Several Odonata studies on Lombok Island still focus on forest and river habitat types. This causes the diversity of this insect group to be unknown in other habitats such as rice fields. This research aims to explore the richness of dragonfly species in the rice field ecosystem of Perian village, Montong Gading subdistrict, East Lombok district. Sample collection was carried out in May – June 2022. Dragonfly searches were carried out in the morning from 08.00 – 12.00, and in the afternoon from 14.00 – 18.00 on two transects determined purposively. The odonata found were documented using a digital camera, and captured using insect nets. Samples that were successfully collected were identified to the species taxon. The total odonata we found were 2 suborders, 5 families and 11 species. The suborder Zygoptera is the group with the highest species richness. For families, Libellulidae and Coenagrionida are the families with the highest species richness compared to other families. Of the 11 species that we found, 1 species is endemic, namely Euphaea lara lombokensis. Compared with the results of previous research conducted in Suranadi and Batu Bolong River, there are 5 species which are new records. The five species are Copera ciliata, Rhinocypha bisignata, Ischnura senegalensis, Ischnura heterosticta, and Brachythemis contaminata. The results of this study indicate that there are more species from the Odonata order on Lombok Island compared to previous reports.